Annual plant reviews, Volume 19: Plant Epigenetics - Meyer, Peter (Blackwell, 2012)
"This volume provides a comprehensive overview of epigenetic mechanisms and biological processes in plants, illustrating the wider relevance of this research to work in other plant science areas and on non-plant systems. It discusses recent advances in our knowledge of basic mechanisms and molecular components that control transcriptional and post-transcriptional silencing, an understanding of which is essential for